EFFECTS OF STUDENT-LED SEMINARS ON SECONDARY SCHOOL STUDENTS’ ACADEMIC ACHIEVEMENT IN FINANCIAL ACCOUNTING IN ABIA STATE (NAU Journal of Technology and Vocational Education, 2024)
This study determinedthe effect of Student-Led Seminars (SLS) on academic achievement inFinancial Accounting among secondary school students in Abia State. Two research questionsguided the study and three null hypotheses were tested. Quasi- experimental research designspecifically; pre-test, post-test non-equivalent control group design was adopted for the study.Population comprised the entire 1,098 students offering Financial Accounting in publicsecondary schools in Abia state. A purposive sampling technique was used to draw a sample of100 SS1 Financial Accounting students. Financial Accounting Achievement Test (FAAT) wasused for data collection. The face and content validity of the instrument were established usingthree experts, while Kudder-Richardson Formula 20 (KR-20) was used to establish the reliabilityof coefficient of 0.98. Mean and standard deviation were used to answer the research questionswhile Analysis of Covariance (ANCOVA) was used to test the null hypotheses. Findings of thestudy revealed among others that SLS is more effective in enhancing students’ academicachievement in Financial Accounting thanthe conventional teaching methods (CTM); which alsoenhanced academic achievement ability of female students than males in Financial Accounting.It was, therefore, recommended among others that Financial Accounting teachers should usemore of SLS in teaching the subject to facilitate better understanding and performance ofstudents.
Keywords: Student- Led Seminars, Conventional Teaching Method, Academic Achievement, Financial Accounting, Gender.